SOUR MILK FORMULAS IN NUTRITION OF INFANTS - E.F. Lukushkina; N.V. Kutilova; O.K. Netrebenko ("Paediatrician" Publishers LLC, 2010)
Health-giving properties of fermented food are related to the fact, that acid medium improves assimilation of protein and fat, increases absorption of iron and zinc, improves digestion. But the kefir and other sour milk food based on the whole milk can't be used in nutrition of infants as human milk substitute because of high content of protein, high osmolarity, deficiency of vitamins and microelements. The article describes the results of clinical approbation of new modern sour milk formula «NAN sour milk», containing proper amount of high-quality protein (OptiPro), enriched with lactalbumin and all sufficient vitamins and microelements. This mixture contains also probiotics (B. lactis), providing high functionality of this food. Key words: infants, sour milk formula, nutrition.(Voprosy sovremennoi pediatrii - Current Pediatrics. 2010;9(1):136-141)